Use of non-sterile gloves in the ward environment: an evaluation of healthcare workers' perception of risk and decision making. Issue 3 (May 2020) - Flores, Ashley; Wrigley, Martha; Askew, Peter; Craig, Rachel; Egan, Bernadette; Towey, Linda; Shawe, Jill
Background: Studies have found that inappropriate use of non-sterile gloves (NSG) can affect hand hygiene compliance; the main risks are missing opportunities for hand hygiene and gloves being a vector for microbial transmission. Aim: The aims of this study were to explore the accuracy of healthcare worker (HCW) risk assessment and decision making regarding the use of NSG. Methods: The study was conducted in two acute NHS Trusts and a community social enterprise. A cross-sectional survey was carried out, followed by qualitative semi-structured interviews. Findings: There were highly significant differences at the 95% probability level between staff groups, unqualified staff being significantly more likely than qualified staff to report NSG use when not indicated ( P < 0.0001). The primary motivating factor for staff to wear NSG was for personal protection; the secondary factor being the protection of patients. Staff were also motivated by a desire to create an image of professionalism. Respondents were more likely to follow the lead of seniors in their own profession. Discussion: The results suggest a necessity for change interventions aimed at unqualified staff such as healthcare assistants (HCAs). It would be beneficial to review the indications for glove use and amend organisational policies accordingly. Leaders in each professional staff group would be required to influence practice across organisations, taking into account motivating factors, and in association with multi-modal interventions to improve practice.